Efektivitas Komunikasi Interpersonal Pelatih dalam Membentuk Karakter Siswa Sekolah Sepakbola di Kota Palembang - Sunarto Sunarto; Ratu Mutialela Caropeboka (Training & Research Institute - Jeramba Ilmu Sukses, 2020)
This study aims to analyze the effectiveness of interpersonal communication between trainers and students in shaping student character. The trainer's interpersonal communication effectiveness variables include: material, method, and time; while the student character variables are limited to: religious, honest, hard work, disciplined, and nationalist. Data analysis in this study used descriptive statistical analysis and inferential analysis. Descriptive statistical analysis is carried out to present research data in the form of tables or graphs, while inferential statistical analysis uses Structural Equation Modeling (SEM), which functions to test research hypotheses and various assumptions that must be met. The results of the study based on the statistical analysis of the structural equation model (Structural Equation Modeling) obtained a t-value of 4.56 > 1.96 and the Standardized Solution of 0.50. This means that it is concluded that the effectiveness of coach interpersonal communication has a positive and significant effect in shaping the character of football school students in the city of Palembang. The effectiveness of the coach's interpersonal communication has a direct effect of 50 percent in shaping the character of students. The higher the effectiveness of interpersonal communication between trainers and students, the more it will improve the character building of students, so that later students with religious, honest, hard-working, disciplined and nationalist characters are formed based on Pancasila.